2008
DOI: 10.2147/ndt.s2286
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eating disorders and eating attacks in narcolepsy

Abstract: Narcoleptic patients suffer frequently from obesity and type II diabetes. Most patients show a defi cit in the energy balance regulating orexinergic system. Nevertheless, it is not known, why narcoleptic patients tend to be obese. We examined 116 narcoleptic patients and 80 controls with the structured interview for anorectic and bulimic eating disorders (SIAB) to test the hypothesis that typical or atypical eating attacks or eating disorders may be more frequent in narcoleptic patients. No difference in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
1
0
1
Order By: Relevance
“…The final one of the 11 studies that we qualitatively reviewed compared binge eating in people with or without narcolepsy. This study found no difference in the prevalence of BED or BN in 196 people with only narcolepsy in comparison to those without narcolepsy/cataplexy (63).…”
Section: Studies That Were Not Included In a Meta-analysiscontrasting
confidence: 76%
See 1 more Smart Citation
“…The final one of the 11 studies that we qualitatively reviewed compared binge eating in people with or without narcolepsy. This study found no difference in the prevalence of BED or BN in 196 people with only narcolepsy in comparison to those without narcolepsy/cataplexy (63).…”
Section: Studies That Were Not Included In a Meta-analysiscontrasting
confidence: 76%
“…Overall, this qualitatively-reviewed study (63), in combination with the results from our meta-analysis, suggests that only people with narcolepsy accompanied by cataplexy have greater binge eating in comparison to those without narcolepsy/cataplexy. Taken together, the results from our qualitative assessment of the 11 studies that could not be included in a meta-analysis were broadly consistent with the results from our meta-analyses, in that people with binge eating demonstrated more sleep problems than people without binge eating, and that people with a shorter sleep duration or sleep apnea (but not narcolepsy unaccompanied by cataplexy) had a greater occurrence of past or present binge eating behaviors.…”
Section: Studies That Were Not Included In a Meta-analysissupporting
confidence: 55%